Kajian Konektifitas Pulau Tahuna Terhadap Kota-Kota Besar di Tinjau Dari Aspek Angkutan Penumpang Melalui Bandar Udara Sam Ratulangi dan Pelabuhan Manado - Sinaga, Rosita (Warta Penelitian Perhubungan, 2011)
Tahuna Island is a border area which has an opportunity to create a coorperation with neighbour countries in Asia Pasific. It is also a nothem gate as an entrance and exit-way of cargoes and passengers. Tahuna also to be a front porch of the unitary state of The Republic of Indonesia as well as a security belt in nothern area and according to government regulation No. 28/2008, it becomes a regency capital that stated as center of national strategy activities and economic development area that has come facilities to support economic, development area that has some facilities to support economic development, social, culture and education. Sea Transportation to serve Manado and Tahuna is operated ever day, in order to attract national tourist visiting this island. So that, the author will access the efficiency of this transportation and carry out research whose topic is connectivity of Tahuna Island to big cities in Indonesia with regarding transportation of passenger aspect. Keyword : connectivity, transportation, Tahuna Island